The Perceived Impact of Green Microfinance to Influence Micro, Small and Medium Enterprises to Implement Green Activities - Berko, Daniel; Rajaram, Rajendra (International Journal of Environmental, Sustainability, and Social Science, 2026)
The global effort to tackle environmental issues has garnered international momentum However, large firms have received far more attention than MSMEs. Meanwhile, MSMEs have a substantial cumulative effect on the environment Microfinance institutions provide financial and non-financial services to MSMEs, and it is considered that microfinance institutions can help MSMEs transition towards adopting environmentally friendly practices. Hence, the purpose of this study was to explore the perceived contribution of green microfinance to influencing MSMEs to implement green activities. Employing a critical review methodology, this study analyzed green microfinance literature from diverse online library databases including Elsevier, Google Scholar, PROQUEST, EMERALD, Science Direct, Research Gate, IEEE, and JSTOR. This study found that MFIs can influence MSMEs to adopt greener practices by including environmental issues into their goals, strategies, and operations. Sustainable practises were found to be also influenced by MSME owners/managers' mindsets, legislative frameworks, stakeholder pressure, competitive dynamics, perceived benefits, and consumer demand for eco-friendly products. As a recommendation the study proposes that Rural and Community Banks, savings and loans companies, and credit unions should be included in the Environmental and Social Risk Management (ESRM) regulatory framework for green financing within the banking industry to address environmental concerns stemming from MSMEs.